2000
DOI: 10.1046/j.1524-4741.2000.20057.x
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Biopsy in Breast Cancer: An Overview

Abstract: The most powerful predictor of survival in breast cancer is the presence or absence of lymph node metastases. Lymphatic mapping and sentinel node biopsy is a new technique that provides more accurate nodal staging compared to routine histology for women with breast cancer without the morbidity of a complete lymph node dissection. Sentinel lymph node biopsy is a more conservative approach to the axilla that requires close collaboration between the surgical team, nuclear medicine, and pathology. National trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…2 Sentinel lymph node biopsy has replaced axillary lymph node dissection in patients with a low risk of axillary nodal metastases because of decreased morbidity. [3][4][5][6][7] Sentinel lymph node status is a representative indicator for the entire lymph node basin. However, false-negative results of sentinel lymph node biopsy have been found.…”
mentioning
confidence: 99%
“…2 Sentinel lymph node biopsy has replaced axillary lymph node dissection in patients with a low risk of axillary nodal metastases because of decreased morbidity. [3][4][5][6][7] Sentinel lymph node status is a representative indicator for the entire lymph node basin. However, false-negative results of sentinel lymph node biopsy have been found.…”
mentioning
confidence: 99%
“…The results of these major studies (including the very small number of cases with failed SND mapping) and the reported overviews of the SND approach 11,13,17 were used to produce a weighted average for the sensitivity of SND to use in the model. Using this method of compositing, a sensitivity of approximately 0.92 was estimated for SND.…”
Section: -10mentioning
confidence: 99%
“…The details of the SND procedure have been well documented and a variety of techniques have been used and continue to be developed. [5][6][7][8][9][10][11][12][13][14][15][16][17] By assessing the status of the first echelon draining lymph node (i.e., the "sentinel" lymph node) of the primary tumor, SND identifies patients who require an AND. However, caution is warranted because the false-negative (FN) rate for SND, albeit small, may have an impact on survival.…”
mentioning
confidence: 99%
“…Radioguided SLN biopsy in breast cancer entails peritumoural injection of 99m Tc, lymphoscintigraphy and node identification during surgery guided by gamma probe [2]. In early-stage breast carcinoma, SLN biopsy has replaced complete axillary lymph node dissection, as analysis of the SLN accurately predicts the status of all axillary nodes in more than 95% of cases with minimal morbidity [3].…”
Section: Introductionmentioning
confidence: 99%